EFEKTIVITAS SISTEM KATALOG ONLINE (OPAC) TERHADAPPEMUSTAKA DI PERPUSTAKAAN NASIONAL RI DENGAN MENGGUNAKAN MODEL DELONE AND MCLEAN IS SUCCESS MODEL - Teguh Gondomono (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2016)
The Online Public Access Catalogue (OPAC) as a part of library information system serves as online information retrieval system for library users. This paper is aimed at finding out factors affecting the efectivity of OPAC for the National Library of Indonesia’s users’ use through the methodology of DeLone and McLean IS Success Model. Data used in this study is primary data obtained through questionnaire spread to National Library of Indonesia’s users who use online catalogue to find information. Data analysis is done by using Path Analysis method in Analysis of Moment Structure (AMOS) program. The analysis result of the tested research model shows that information quality factor has a positive impact on users’ satisfaction with Critical Ratio (CR) of 2.373 and Probability (P) of 0.018. Service quality has a positive impact on system use with CR value of 4.393 and P value of 0.00. Service quality has a positive impact on user satisfaction with 10.674 of CR value and 0.00 of P value. System use has an impact on net benefit with 2.612 value of CR and 0.009 of P value. User satisfaction has a positive impact on net benefit with CR value of 5.621 and P value of 0.00. Factor that has significant impact on user satisfaction is service quality with the CR value of 10.674 and P value of 0.00.